2022
DOI: 10.1017/s0007114522000721
|View full text |Cite
|
Sign up to set email alerts
|

The whole blood DNA methylation patterns of extrinsic apoptotic signalling pathway-related genes in autoimmune thyroiditis among areas with different iodine levels

Abstract: Autoimmune thyroiditis (AIT) has a complex etiology and the susceptibility to it is determined by a combination of genetic and environmental factors, although these are not yet fully understood. The present research aimed to explore the DNA methylation patterns in whole blood of extrinsic apoptotic signaling pathway related genes in AIT among areas with different iodine levels. We selected the iodine-fortification areas (IFA), iodine-adequate areas (IAA) and water-based iodine-excess areas (IEA) from Shandong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…One study in the elderly showed that iodine could not modulate the global DNA methylation profile of leukocytes (43) , and another study in animals showed that IE did not change the global methylation levels in lymphocytes (44) . Our previous studies have shown that different iodine levels could affect the methylation patterns of DAPK1 and ITGA6 (45,46) . This study further confirms that iodine status could affect the methylation levels of intrinsic apoptosis genes.…”
Section: Discussionmentioning
confidence: 99%
“…One study in the elderly showed that iodine could not modulate the global DNA methylation profile of leukocytes (43) , and another study in animals showed that IE did not change the global methylation levels in lymphocytes (44) . Our previous studies have shown that different iodine levels could affect the methylation patterns of DAPK1 and ITGA6 (45,46) . This study further confirms that iodine status could affect the methylation levels of intrinsic apoptosis genes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of iodine presence in 5-ISA-fortified lettuce, there is little known about potential effects of iodine on DNA methylation in human cells although iodine affects thyroid function and play a role in thyroid cancer and other thyroid disease [ 23 ]. Nevertheless, iodine excess has been shown to affect DNA methylation of selected genes in blood of patients with autoimmune thyroiditis [ 24 , 25 ]. Hence, potential epigenetic effects of iodine cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that altered patterns of DNA methylation play a role in the progression of cancer and pathogenesis of other disease [ 16 ]. Interestingly, polyphenols from lettuce, iodine, and salicylic acid were all reported to exert certain epigenetic effects [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%